A spectral dynamic stiffness method for free vibration analysis of plane elastodynamic problems. (15th March 2017) - Liu, X.; Banerjee, J.R.
Abstract: A highly efficient and accurate analytical spectral dynamic stiffness (SDS) method for modal analysis of plane elastodynamic problems based on both plane stress and plane strain assumptions is presented in this paper. First, the general solution satisfying the governing differential equation exactly is derived by applying two types of one-dimensional modified Fourier series. Then the SDS matrix for an element is formulated symbolically using the general solution. The SDS matrices are assembled directly in a similar way to that of the finite element method, demonstrating the method's capability to model complex structures. Any arbitrary boundary conditions are represented accurately in the form of the modified Fourier series. The Wittrick-Williams algorithm is then used as the solution technique where the mode count problem ( J 0 ) of a fully-clamped element is resolved. The proposed method gives highly accurate solutions with remarkable computational efficiency, covering low, medium and high frequency ranges. The method is applied to both plane stress and plane strain problems with simple as well as complex geometries. All results from the theory in this paper are accurate up to the last figures quoted to serve as benchmarks. Abstract : Highlights: SDSM formulation for plane elastodynamic problems with arbitrary BCs. Theory applicable to both plane stress and plane stress vibrations. Analytical method but versatile for complex structures. Providing highly accurate solutions very efficiently for the whole frequency range. Offering an idea tool for parametric and optimisation studies of structures.